Private TVET in Africa: Understanding the Context and Managing Alternative Forms Creatively! - Akoojee, Salim (Journal of Technical Education and Training, 2016)
Since the 1990s, there has been a growing sense from both national policymakers and international agencies of the importance of private Technical and Vocational Education and Training and skills provision in all regions.  This pri-VET sector both through traditional apprenticeship forms and more formal sector oriented approaches have become an essential feature of the contemporary landscape. It is, however, a sector that is largely undocumented and its regulation is thus based on a less than nuanced understanding of its contribution to both the education and training system in general and as a complement to public TVET provisioning. The paper will seek to identify key features of the key trends of what is known about private TVET provision in Africa with a view to understanding the complexity of provision forms and its current importance in the region. It is argued that for this â€˜unconventional education and trainingâ€™ form to take its place in national systems, there is a need for more rigorous research of the sector to ensure that it is able to take its rightful place in national systems. It is expected that this will enable a more thorough examination of regulatory mechanisms used by governments.